Rapid and sensitive determination of Se and heavy metals in foods using electrothermal vaporization inductively coupled plasma mass spectrometry with a novel transportation system - Lan, Guanyu; Li, Xue; Yao, Jijun; Yu, Xiaofeng; Liu, Qinghai; Qiu, Cheng; Mao, Xuefei (Frontiers in Nutrition, 2023)
Rapid, sensitive and simultaneous determination of trace multi-elements in various plant food samples such as grain, oilseed, vegetable and tea is always a challenge thus far. In this work, a rapid determination method for Se, Cd, As and Pb in food samples by inductively coupled plasma mass spectrometry (ICPMS) using slurry sampling electrothermal vaporization (SS-ETV) was developed. To improve the analytical sensitivity and precision as well as eliminate the memory effect, a gas turbulator line and signal delay device (SDD) were for the first time designed for the graphite furnace (GF) ETV coupled with ICPMS. The signal acquisition parameters of ICPMS, ashing and vaporization conditions, and the flow rates of carrier and gas turbulatores were investigated for Se, Cd, As and Pb in food samples. Under the optimized conditions, the limits of determination (LODs) for Se, Cd, As and Pb were 0.5 ng g-1, 0.3 ng g-1, 0.3 ng g-1 and 0.6 ng g-1, respectively; linearity (R2) in the range of 1 to 4000 ng g-1 was > 0.999 using the standard addition method. This method was used to analyze 5 CRMs including rice, tea and soybeans, and the determination values of this method were within the range of the certificate values. The recoveries of Se, Cd, As and Pb in plant food matrices including grain, oilseed, vegetable and tea samples were 86-118% compared to the microwave digestion ICP-MS method; and the relative standard deviations (RSDs) were 1.2-8.9% for real food sample analysis, proving a good precision and accuracy for the simultaneous determination of multi-elements. The analysis time was less than 3 min, slurry preparation time <5 min without sample digestion process. The proposed direct slurry sampling ICPMS method is thus suitable for rapid and sensitive determination of Se, Cd, As and Pb in food samples with advantages such as simplicity, green and safety, as well as with a promising application potential in detecting more elements to protect food safety and human health.